1996
DOI: 10.1002/hep.510240617
|View full text |Cite
|
Sign up to set email alerts
|

Ascitic Fluid Adenosine Deaminase Insensitivity in Detecting Tuberculous Peritonitis in the United States

Abstract: Tuberculous peritonitis, although common in Third World countries, remains an uncommon cause of ascites in the United States. Ascitic fluid adenosine deaminase (ADA) activity has been proposed as a useful diagnostic test. The aim of this retrospective study was to determine the clinical utility of ascitic fluid ADA activity in diagnosing tuberculous peritonitis in a U.S. patient population. A total of 368 ascitic fluid specimens from a well-characterized ascitic fluid bank, including tuberculous peritonitis (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
1
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(92 citation statements)
references
References 27 publications
1
86
1
4
Order By: Relevance
“…Previous studies reported that the ADA assay has a sensitivity of 100 % and specificities in the range of 92-100 % for the diagnosis of TB peritonitis (Voigt et al, 1989;Fernandez-Rodriguez et al, 1991;Gupta et al, 1992;Brant et al, 1995). In contrast, Martinez-Vazquez et al (1986) found that the ADA assay was not specific for the diagnosis of TB peritonitis, and other studies showed that the sensitivity of the ADA assay was significantly lower for patients with underlying liver cirrhosis (Sathar et al, 1995;Hillebrand et al, 1996), a finding not observed in our current study. Although ADA levels were elevated in other infectious or inflammatory disorders, definite cut-off values were associated only with TB peritonitis.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies reported that the ADA assay has a sensitivity of 100 % and specificities in the range of 92-100 % for the diagnosis of TB peritonitis (Voigt et al, 1989;Fernandez-Rodriguez et al, 1991;Gupta et al, 1992;Brant et al, 1995). In contrast, Martinez-Vazquez et al (1986) found that the ADA assay was not specific for the diagnosis of TB peritonitis, and other studies showed that the sensitivity of the ADA assay was significantly lower for patients with underlying liver cirrhosis (Sathar et al, 1995;Hillebrand et al, 1996), a finding not observed in our current study. Although ADA levels were elevated in other infectious or inflammatory disorders, definite cut-off values were associated only with TB peritonitis.…”
Section: Discussioncontrasting
confidence: 99%
“…13 Studies from a tuberculosis endemic area like South Africa have reported sensitivity and specificity exceeding 92% for this non-invasive test, 35 whereas the study from the United States showed that the ascitic fluid ADA activity has good accuracy but poor sensitivity and imperfect specificity, where the prevalence of tuberculosis is low and underlying cirrhosis is common. 36 Gamma (γ) interferon, secreted by antigen-triggered CD4+ lymphocytes, is a key lymphokine that activates macrophages, increasing their bactericidal activity against Mycobacterium tuberculosis. 34 Although the sensitivity and specificity of ascitic fluid ADA and γ-interferon activity are high in tuberculous peritonitis, their activities have been reported to be significantly lower in patients with low ascitic fluid protein concentration and in patients with AIDS, explained by a low lymphocyte activity due to the CD4+ lymphocyte depletion in HIV infection.…”
Section: Diagnosis Of Abdominal Tuberculosismentioning
confidence: 99%
“…6 Laparoscopic biopsies and ultrasound or CT-guided fine needle aspiration cytology provide definitive diagnosis of tuberculous peritonitis. 7,8 …”
Section: Cirrhosis-a Risk Factor For Tuberculosismentioning
confidence: 99%